Level structure of 74As from the 72Ge (x,np,y) reaction - García Bermúdez, G. J.; Behar, M.; Filevich, Alberto.; Maricotti, M. A. J. (1976)
Fil: García Bermúdez, G. J. Comisión Nacional de Energía Atómica; Argentina